2013
DOI: 10.1105/tpc.113.115998
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Downstream Components of Ubiquitin-Conjugating Enzyme PHOSPHATE2 by Quantitative Membrane Proteomics in Arabidopsis Roots

Abstract: ORCID ID: 0000-0001-5953-4144 (T.-J.C.).MicroRNA399-mediated regulation of the ubiquitin-conjugating enzyme UBC24/PHOSPHATE2 (PHO2) is crucial for Pi acquisition and translocation in plants. Because of a potential role for PHO2 in protein degradation and its association with membranes, an iTRAQ (for isobaric tags for relative and absolute quantitation)-based quantitative membrane proteomic method was employed to search for components downstream of PHO2. A total of 7491 proteins were identified from Arabidopsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
219
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(230 citation statements)
references
References 72 publications
(113 reference statements)
10
219
0
1
Order By: Relevance
“…Root: shoot ratio increases dramatically under drought conditions suggesting that functional responses to reduced soil moisture primarily occur through increased growth of roots, as has been shown suggested by Quezada and Gianoli (2010). Similarly, Huang et al, (2013) also reported that deficiencies of soil water resulted in high root: shoot ratio. Relatively, more biomass was allocated to the root than to the shoot, and plant allocated more resource to the belowground growth.…”
Section: Biomass Partitioning Under Greenhouse Conditionsmentioning
confidence: 50%
See 1 more Smart Citation
“…Root: shoot ratio increases dramatically under drought conditions suggesting that functional responses to reduced soil moisture primarily occur through increased growth of roots, as has been shown suggested by Quezada and Gianoli (2010). Similarly, Huang et al, (2013) also reported that deficiencies of soil water resulted in high root: shoot ratio. Relatively, more biomass was allocated to the root than to the shoot, and plant allocated more resource to the belowground growth.…”
Section: Biomass Partitioning Under Greenhouse Conditionsmentioning
confidence: 50%
“…The traits root biomass at bottom and root shoot ratio had increased values under drought 28.463 and 9.388 respectively. Huang et al, (2013) reported that deficiencies of soil water resulted in high root: shoot ratio. Relatively, more biomass was allocated to the root than to the shoot, and plant allocated more resource to the belowground growth.…”
Section: Effect Of Drought On Root Traits and Biomass Partitioningmentioning
confidence: 99%
“…The P leaf concentration of the mutant pho1 is very diminished while in the roots it has concentrations very similar to those of the wild cultivar, which suggests that this mutant has a defect in the loading of P into the xylem [100,[102][103][104]. By contrast, the pho2 mutant accumulates up to three times more P in the aerial part than the wild cultivar, while the root maintains similar levels, or even slightly lower levels than the wild cultivar [43,101,105,106]. The pho2 mutant could either prevent the transport of P through the phloem, from the aerial part to the root, or have some problem in the regulation of P concentration in the leaves [107].…”
Section: Hormones and Signaling Substances In The Regulation Of Fe Anmentioning
confidence: 84%
“…Multiple lines of evidence indicate that PT proteins undergo several posttranslational modifications in addition to transcriptional regulation (Bayle et al, 2011;Huang et al, 2013;Lin et al, 2013;Park et al, 2014). One key regulatory step is ER exit of PTs to the PM, which is regulated positively by PHF1 and negatively by phosphorylation.…”
Section: Discussionmentioning
confidence: 99%